2015
DOI: 10.4172/2157-7048.1000221
|View full text |Cite
|
Sign up to set email alerts
|

Honeycomb Structures of TiO2-modified Hydroxyapatite Composite for Microbial Filtration Application

Abstract: Honeycomb structures of TiO 2 -modified hydroxyapatite composite (HA/TiO 2 ) were fabricated using extrusion technique. The mixture formulations of HA/TiO 2 extrusion pastes (S1-S4) were investigated to optimize the process. The filtering effectiveness of the HA/TiO 2 honeycombs was evaluated by photocatalytic activity measurement and a bactericidal test. The effects of sintering temperature and honeycomb thickness on photocatalytic and antibacterial activities were additionally studied. The S3 and S4 honeycom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…16 Thus, honeycomb-like TiO 2modified hydroxyapatite composites were prepared through the extrusion technique followed by sintering and exhibited good photocatalytic and antibacterial activities. 17 Kumar et al 18 described the sequential formation of β-Ca 3 (PO 4 ) 2 / TiO 2 composites from precursor solutions and revealed that the mechanical properties are dependent on TiO 2 content. TiO 2 is a semiconducting oxide with three possible crystalline structures (anatase, rutile, and brookite) 6 and a promising material for scaffolds because of its excellent properties, such as: superior corrosion resistance, 16 high chemical and mechanical stability, 18 biocompatibility and bioactivity,19 antibacterial potential,20 and capacity to increase cellular proliferation.21,22 Therefore, TiO 2 is employed in many applications, including paints, catalysts, sensors, cosmetics, wound dressings,23 and bone scaffolds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Thus, honeycomb-like TiO 2modified hydroxyapatite composites were prepared through the extrusion technique followed by sintering and exhibited good photocatalytic and antibacterial activities. 17 Kumar et al 18 described the sequential formation of β-Ca 3 (PO 4 ) 2 / TiO 2 composites from precursor solutions and revealed that the mechanical properties are dependent on TiO 2 content. TiO 2 is a semiconducting oxide with three possible crystalline structures (anatase, rutile, and brookite) 6 and a promising material for scaffolds because of its excellent properties, such as: superior corrosion resistance, 16 high chemical and mechanical stability, 18 biocompatibility and bioactivity,19 antibacterial potential,20 and capacity to increase cellular proliferation.21,22 Therefore, TiO 2 is employed in many applications, including paints, catalysts, sensors, cosmetics, wound dressings,23 and bone scaffolds.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, recent studies have emphasized a good interaction between CPs and titanium dioxide (TiO 2 ), as well as high biocompatibility, which recommend such combinations for bone engineering 16 . Thus, honeycomb‐like TiO 2 ‐modified hydroxyapatite composites were prepared through the extrusion technique followed by sintering and exhibited good photocatalytic and antibacterial activities 17 . Kumar et al 18 described the sequential formation of β‐Ca 3 (PO 4 ) 2 /TiO 2 composites from precursor solutions and revealed that the mechanical properties are dependent on TiO 2 content.…”
Section: Introductionmentioning
confidence: 99%
“…By modifying HA with TiO 2 , HA can adsorb molecules which will then be broken down by TiO 2 . HA-TiO 2 composites with a ratio of 50-50 showed a bacterial decomposition of about 50% after 2 h of UV exposure [38,39]. In other research, the HA-TiO 2 composite with 60% TiO 2 showed good antibacterial activity [40].…”
Section: Introductionmentioning
confidence: 83%
“…During this process, negative electrons generate O 2− , and the positive electron holes generate the hydroxyl radicals which attack and kill the bacteria and viruses [ 145 ]. Naruporn et al [ 146 ] fabricated a honeycomb structure of the TiO 2 -decorated hydroxyapatite composite (HA/TiO 2 ), and this membrane showed 90–95% antibacterial efficacy against E. coli and S. aureus when exposed to UV light for 6 h. Recently, metal organic frameworks (MOFs) have been applied as a bactericidal agent, where ROS is generated from metal ions to kill bacteria [ 147 ]. ZIF-8, MOF-199, and Ag-MOF were tested by incorporating in the cellulose filters, and the incorporated filter showed ~99.9% bactericidal efficacy against E. coli [ 148 ].…”
Section: Multi-functional Filter Developmentmentioning
confidence: 99%